Study of Disease Pattern among Personnel Deployed in Mali focusing on Pre-Deployment Health Preparedness (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Demographic and epidemiological transition has altered disease patterns globally. Adequate knowledge on disease patterns will provide scope for pre-deployment health preparedness. Providing important information regarding disease patterns, correct diagnosis of a disease and its management contribute in effective patient care system.Objective: To find out the pattern of disease existing in level-I hospital of the UN peacekeepers in Mali.Materials and Methods: This cross-sectional analytical study was carried out in the Level-I Hospital for the period of 01(one) year from 1st July 2018 to 30th June 2019. Sample size was 2193. Data were collected from the patients reported sick in the hospital during the specified period. All patients are divided in two categories; Outdoor patients and Indoor patients. We have classified the diseases into four broad categories: (1) Injury, (2) Non-infectious Diseases, (3) Infectious Diseases and (4) Sexually Transmitted Infections. All the collected data were edited and analyzed.Results: Disease patterns in the level-I hospital of UN peacekeepers are not the same as per the disease prevalence of Mali. Disease patterns in UN peacekeeper mainly includes musculoskeletal low back pain, Peptic Ulcer Disease, Dry eye syndrome, Upper Respiratory Tract infections, Diarrheal diseases, Urinary tract infections and Malaria.Conclusion: Pre-deployment health education to the UN peacekeeper including the healthcare services provider contributes to the positive influence on health. Pre-deployment health training should be focused on disease patterns occurring in Level-I hospital, at the same time prevalence of diseases of the specific country has to be taken into account.JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 18-21